Studi Penggunaan Carboplatin untuk Penderita Kanker Payudara di RUMKITAL Dr. Ramelan Surabaya - Giovani, Alfin; Hasmono, Didik; Surdijati, Siti; Semedi, Joko (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2020)
Cancer is an abnormal growth of new cells that grow beyond normal limits. Cancer can metastasize by attacking parts of the body and spread to other organs. The prevalence of cancer Indonesian’s people in 2013 is estimated at 347,792. Breast cancer is the most common cancer in women with a percentage of 23%. Breast cancer is the second most common cancer with death after cervical cancer. Breast cancer is divided according to histologic subtype to Ductal Carcinoma in Situ (DCIS) and Lobular Carcinoma in Situ (LCIS). Carboplatin is a platinum analog cancer drug that belongs to the class of antineoplastic agents. Carboplatin doses used in AUC 6 (i.v) breast cancer chemotherapy for 1 cycle with 21 days to 6 cycle times. This research was conducted observasional with descriptive research design and retrospective data retrieval. The purpose of this study was to know the profile of carboplatin as an anti-cancer drug that is expected to provide safe treatment. This research was conducted at Dr. RUMKITAL Ramelan Surabaya with the number of inclusion of 30 patients in the period January 1, 2017 - December 31, 2017. From the results of this study obtained the use of single carboplatin as much as 7% and a combination of 93%. Patients with chemotherapy administered without surgery and surgery were 73% and 27%, respectively. Toxicity of nausea and vomiting happen as much as 42% and pain as much as 19%.